(untitled) (Research, Society and Development, 2021)
Objective: To describe the nurse’s performance in the brain death process and in the donation of organs and tissues. Method: This is a study of narrative review of the literature with an exploratory qualitative approach, focused on the role of nurses in cases of brain death and organ donation. Results: 14 articles were selected according to the theme, after the interpretation divided into two categories: nursing conduct facing and possible cause of brain death and facing a family of patients with brain death. Conclusion: The nurse presents as an optimizer of the organ and tissue donation process and an important role in the active search and maintenance of patients with brain death, in addition to articulating with family members in an attempt to obtain a favorable decision to donate. The nursing interview showed that it is a predictive instrument that directs the effective and humanized way and is capable of avoiding a family refusal to make decisions regarding donations.